2017
DOI: 10.18632/oncotarget.16343
|View full text |Cite
|
Sign up to set email alerts
|

NFkB is essential for activin-induced colorectal cancer migration via upregulation of PI3K-MDM2 pathway

Abstract: Colorectal cancer (CRC) remains a common and deadly cancer due to metastatic disease. Activin and TGFB (TGFβ) signaling are growth suppressive pathways that exert non-canonical pro-metastatic effects late in CRC carcinogenesis. We have recently shown that activin downregulates p21 via ubiquitination and degradation associated with enhanced cellular migration independent of SMADs. To investigate the mechanism of metastatic activin signaling, we examined activated NFkB signaling and activin ligand expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 53 publications
3
41
0
2
Order By: Relevance
“…9, 13, 44). As mentioned in Introduction, NF-kB is activated in KRAS-mutated colorectal cancer (9,10). We indeed demonstrated that MIRTX could directly bind to the 3 0 -UTR region of CXCR2 and PIK3R1 mRNAs and suppress protein expression of both genes in KRAS-mutated colorectal cancer cells, DLD1 and SW480.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…9, 13, 44). As mentioned in Introduction, NF-kB is activated in KRAS-mutated colorectal cancer (9,10). We indeed demonstrated that MIRTX could directly bind to the 3 0 -UTR region of CXCR2 and PIK3R1 mRNAs and suppress protein expression of both genes in KRAS-mutated colorectal cancer cells, DLD1 and SW480.…”
Section: Discussionsupporting
confidence: 68%
“…Recent evidence indicates that the NF-kB transcription factor is constitutively activated in KRAS-mutant colorectal cancer (9,10). Therefore, targeting NF-kB signaling pathway represents a promising strategy against KRAS-mutant colorectal cancer, although this has not been successful so far in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of NF-κB could repress these chemokines, such as MCP-1, VEGF, IL-8 and Gro-α [138][139][140][141]. Moreover, PI3K promoted the transcription of MDM2 and degradation of p21 in an NF-κB-dependent manner, which can promote colon cancer cell migration [142].…”
Section: The Nf-κb Signaling Pathway a Central Mediator Between Inflmentioning
confidence: 99%
“…Nuclear Factor κB (NF-κB) pathway is well known for its variety of functions on cellular responses and disease development. Abnormal activation of NF-κB pathway mediates a wide range of cellular processes related to tumorigenesis, including reduction of cell apoptosis, oncogene mutations and immune stimulation in multiple types of human cancers [8][9][10]. Activation of NF-κB in cancers is most likely though either inflammatory stimulation such as tumor necrosis factor (TNF) or upstream regulator such as NF-kB-inducing kinase (NIK), respectively [11,12].…”
mentioning
confidence: 99%